2019
DOI: 10.1016/j.celrep.2018.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Lengthening of Telomeres through Two Distinct Break-Induced Replication Pathways

Abstract: Highlights d An assay to visualize ALT telomere DNA synthesis in APBs d APBs are functionally important for ALT DNA synthesis d RAD52 promotes telomere D-loops in vitro and ALT DNA synthesis in APBs d A RAD52-independent BIR pathway is responsible for C-circle formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
271
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(305 citation statements)
references
References 62 publications
15
271
0
Order By: Relevance
“…Examples included MoTeRs that were truncated at specific nucleotide positions, or copies flanked by variant repeat tracts with unusual (TTTGGG) n TTAGGG configurations. The operation of BIR was not all that surprising because broken interstitial telomeres should be structurally equivalent to the shortened telomeres that result from experimental deletion of the telomerase (TERT) and, in yeasts and humans, BIR is the default repair pathway for telomeres thus compromised [8890]. Moreover, M. oryzae TERT knockout strains preferentially repair their telomeres via BIR, wherein critically shortened telomeric 3’ ends invade their own subtelomeres at a very short TTAGGG motif (with as few as 1.5 repeats) to form a D-loop.…”
Section: Resultsmentioning
confidence: 99%
“…Examples included MoTeRs that were truncated at specific nucleotide positions, or copies flanked by variant repeat tracts with unusual (TTTGGG) n TTAGGG configurations. The operation of BIR was not all that surprising because broken interstitial telomeres should be structurally equivalent to the shortened telomeres that result from experimental deletion of the telomerase (TERT) and, in yeasts and humans, BIR is the default repair pathway for telomeres thus compromised [8890]. Moreover, M. oryzae TERT knockout strains preferentially repair their telomeres via BIR, wherein critically shortened telomeric 3’ ends invade their own subtelomeres at a very short TTAGGG motif (with as few as 1.5 repeats) to form a D-loop.…”
Section: Resultsmentioning
confidence: 99%
“…Like its counterpart in yeast, the mammalian ortholog of Sgs1, the Bloom syndrome helicase (BLM), has been implicated in the mammalian ALT pathway. Depletion by siRNA in ALT-positive cells results in the reduction of ALT-associated phenotypes such as the accumulation of extrachromosomal telomeric repeats in the form of partially single-stranded Crich circles, termed C-circles, and G2/M telomere synthesis (O'Sullivan et al 2014;Pan et al 2019;Zhang et al). Notably, BLM also plays an important role at telomeres in cells that do not utilize ALT to maintain their telomeres, acting to facilitate telomere replication and suppressing rapid telomere deletions (Stavropoulos et al 2002;Sfeir et al 2009;Barefield and Karlseder 2012;Zimmermann et al 2014 ;Drosopoulos et al 2015;Pan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed we found that (i) the depletion of POLD3 rescues lethality upon DSB in active genes in a SETX-depleted background, (ii) excessive DNA synthesis takes place at DSBs upon SETX depletion despite reduced RAD51 loading (Cohen et al, 2018), (iii) this repair-associated DNA synthesis depends on POLD3 and BLM, and (iv) BIR genomic signature correlates with expression levels of SETX, POLD3 and BLM in cancer patient samples. So far, POLD3-dependent BIR in human cells has been mainly involved in Alternative Lengthening of Telomeres (ALT) (Dilley et al, 2016;Min et al, 2019;Porreca et al, 2020;Roumelioti et al, 2016;Sobinoff et al, 2017;Zhang et al, 2019) and at one-ended DSBs, collapsed replication forks by a process also known as MiDAS (Mitotic Induced DNA synthesis) (Bhowmick et al, 2016;Costantino et al, 2014;Minocherhomji et al, 2015;Sotiriou et al, 2016). Moreover, BIR has been previously proposed to account for specifics genomic signatures, including tandem duplication, on the human genomes (Carvalho et al, 2013;Costantino et al, 2014;Hastings et al, 2009aHastings et al, , 2009bWillis et al, 2015;Zhang et al, 2009), suggesting that BIR indeed occurs in some context in mammalian cells.…”
Section: Blm and Hencementioning
confidence: 99%
“…Finally, BLM (or its yeast counterpart sgs1) was also proposed to contribute to Break-Induced Replication (BIR) (Mehta et al, 2017) and BIR-like pathways such as during Alternative Lengthening of Telomeres (ALT) that elongates telomeres in telomerase negative cells (Dilley et al, 2016;Lu et al, 2019;Min et al, 2019;Roumelioti et al, 2016;Silva et al, 2019;Sobinoff et al, 2017;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%